Searching through the shelves of the «storia» of Francesco II Maria della Rovere’s library - Elisa Tosi Brandi (Bibliothecae.it)
This contribution considers a selection of volumes from the Durantine book collection that belonged to Francesco Maria II Della Rovere. The theme of the research is the 10 shelves dedicated to ‘history’ where once there were more than 1700 books that represented about 1/10 of the more than 13,000 of the original library divided into 12 subject groups. The selection of books covered by the descriptions and thoughts proposed here, identified thanks to the fifth volume dedicated to the Storia, edited by Simona De Gese and Fiammetta Sabba, of the work conceived by Alfredo Serrai and edited by Fiammetta Sabba on the Biblioteca di Francesco Maria II Della Rovere, was intended to connect the personal interests of Francesco Maria II with the national and international political events that involved the Duchy of Urbino in a period of great changes that were also reflected in the choice of books for the libraria. In fact, sifting through the books that the duke purchased with the advice of the Jesuit Paolo Beni, one discovers editorial novelties that reflect the tastes of an era as well as the ambitions of the duke, who was engaged in the years of the establishment of this modern printed library in a policy of relaunching his dynasty, which he felt he had to anchor more firmly to the origins of the prestige of the house and, therefore, to the cultural operations elaborated at the time of Federico Montefeltro, as well as the military ones carried out by Francesco Maria I.